Isolated unilateral medial rectus palsy: a rare presentation of midbrain infarction in a child - Modage, Anita; Gaonkar, Virendra; Pereira, Myla Isha; Lolyekar, Aishwarya Vijay (International Journal of Contemporary Pediatrics, 2024)
This case study describes a rare instance of isolated unilateral medial rectus palsy in a young patient with Fabry disease, an X-linked lysosomal storage disease. A five-and-a-half-year-old child did not exhibit any other symptoms associated with a stroke, other than abrupt onset diplopia and a pronounced left-eye squint. Isolated medial rectus palsy as a sole presentation of midbrain infarct is a rare entity. Fabry disease is associated with an increased risk of ischemic strokes in patients because of the build-up of glycosphingolipids in the vascular endothelium. This case emphasizes how crucial it is to conduct early neuroimaging and to have a high index of suspicion when dealing with uncommon neurological presentations, particularly in individuals who have underlying genetic conditions like Fabry disease.